Behavior analysis by model slope experiment of artificial rainfall - M. C. Park (Natural Hazards and Earth System Sciences, 2016)
In this study, we performed a model slope experiment with rainfall seepage, and the results were compared and verified with the unsaturated slope stability analysis method. In the model slope experiment, we measured the changes in water content and matric suction due to rainfall seepage, and determined the time at which the slope failure occurred and the shape of the failure. In addition, we compared and verified the changes in the factor of safety and the shape of the failure surface, which was calculated from the unsaturated slope stability analysis with the model experiment. From the results of experiment and analysis, it is concluded that the unsaturated slope stability analysis can be used to accurately analyze and predict rainfall-induced slope failure. It is also concluded that in seepage analysis, setting the initial conditions and boundary conditions is very important. If engineers will use the measured porewater pressure or matric suction, the accuracy of analysis can be enhanced. The real-time monitoring system of porewater pressure or matric suction can be used as a warning of rainfall-induced slope failure.